Processing and characterisation of Calcium SulfoAluminate (CSA) eco-cements coated with a hybrid organo-inorganic material for photocatalytic applications - Morales-Cantero, Alejandro; Cabeza-Díaz, Aurelio; Gómez-de-la-Torre, María de los Ángeles; García-Aranda, Miguel Ángel; Santacruz-Cruz, María Isabel (My University, 2015)
On the one hand, Calcium SulfoAluminate (CSA) eco-cements are receiving increasing attention since their manufacture produces up to 40% less CO2 than ordinary Portland cement (OPC). In addition, they show interesting properties such as high early-age strengths, short setting times, impermeability, sulfate and chloride corrosion resistance and low alkalinity. On the other hand, water treatment is a key issue and it will become much more important in the decades ahead. We have developed a photocatalytic material capable to degrade contaminants in water, under both UVA and visible radiations. In both cases, it works more effectively than nano-TiO2 (Evonik P25). The environmental benefits of the use of CSA eco-cements with a photocatalyst are two folds: the photocatalytic treatment of contaminated water, and lower CO2 emissions because of the use of eco-cements rather than OPC. However, before preparing the coating, different parameters need to be under control. This includes the effect of the photocatalyst onto the eco-cement (setting time, phase assemblage, and so on), and the effect of the eco-cement on the photocatalyst. This work deals with the processing and characterisation of coatings onto CSA eco-cement pastes, including rheological behaviour, setting time, adhesion, and so on.
Keywords: Fotocatálisis; Cemento; CSA eco-cement; Processing; Water treatment; Photocatalysis